Student 2000 : net-based learning for the next millenium - Synnes, Kåre; Parnes, Peter; Widen, Johnny; Schefström, Dick (Luleå tekniska universitet, Datavetenskap, 1999)
Luleå University of Technology has for the last few years deployed a net-based learning environment, mStar, to distribute courses to students independent of time and geographic distance. The mStar enviroment gives remotely attending students equal possibilities as traditionally attending students to take an active part of a course, as well as enhancing the learning experience for all students. This is made possible through a novel combination of IP-multicast technology and the WWW. This paper reports on experiences gained over a few years of practice and depicts a vision of the next generation of the mStar environment. Godkänd; 1999; 20070402 (johnny)